2011
DOI: 10.1186/1748-5908-6-86
|View full text |Cite
|
Sign up to set email alerts
|

Task shifting and integration of HIV care into primary care in South Africa: The development and content of the streamlining tasks and roles to expand treatment and care for HIV (STRETCH) intervention

Abstract: BackgroundTask shifting and the integration of human immunodeficiency virus (HIV) care into primary care services have been identified as possible strategies for improving access to antiretroviral treatment (ART). This paper describes the development and content of an intervention involving these two strategies, as part of the Streamlining Tasks and Roles to Expand Treatment and Care for HIV (STRETCH) pragmatic randomised controlled trial.Methods: Developing the interventionThe intervention was developed follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 33 publications
0
29
0
Order By: Relevance
“…Since 2007 it has included provision for nurse initiation and re-prescription of ART. This inclusion was based on the results of a large pragmatic randomised controlled trial performed in the Free State Province that showed that nurses were as effective as doctors in providing ART care [9,11,12], and on a second trial in the Western Cape and Gauteng Provinces that evaluated nurse re-prescription of ART [43]. This development was prompted by the urgent need to expand ART services in South Africa.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since 2007 it has included provision for nurse initiation and re-prescription of ART. This inclusion was based on the results of a large pragmatic randomised controlled trial performed in the Free State Province that showed that nurses were as effective as doctors in providing ART care [9,11,12], and on a second trial in the Western Cape and Gauteng Provinces that evaluated nurse re-prescription of ART [43]. This development was prompted by the urgent need to expand ART services in South Africa.…”
Section: Methodsmentioning
confidence: 99%
“…Consistent with our previous experience with PALSA PLUS, some variation in uptake of the management tool by nurses was reported. There was a tendency for nurses who formerly used PALSA PLUS to adopt PC101 and use it regularly, whereas nurses who had not used PALSA PLUS were less likely to begin to use the new management tool routinely [11,12]. Uptake by the trainers was considered excellent, and trainers completed planned sessions in all intervention clinics, some repeating sessions to ensure coverage of most staff.…”
Section: Methodsmentioning
confidence: 99%
“…However, early results from a larger cluster RCT shifting care to nurses in South Africa are also promising and final reporting should add substantively to the evidence-base. 134, 135 …”
Section: Cross-cutting Strategies For Combination Hiv Preventionmentioning
confidence: 99%
“…At the opposite end, the highly functional “optimizing” stage, the regulatory processes are sophisticated and efficient and include the use of technology and data to continuously improve regulatory processes. The ARC CMM delineates stages of functional maturity with real world examples using national regulations, recommendations, and stated obstacles to strengthening nursing and midwifery practices that are referenced in the peer-reviewed and grey literature (ICN, 2007; Miles, Seitio, & McGilvray, 2006; PEPFAR, 2012; Uebel, Fairall, Van Rensburg, Mollentze, & Bachman, 2011; USAID, 2010; Zachariah et al, 2009). Literature which included specific challenges and recommendations for nursing and midwifery regulatory reform in the context of HIV scale-up in the ECSA region was considered highly relevant.…”
Section: Tool Designmentioning
confidence: 99%